DEVELOPMENT TENDENCIES OF THE GENDER POLICY OF THE REPUBLIC OF UZBEKISTAN - Mirzayorova Kamola; Nurutdinova Madinabonu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Gender is a socially applied definition of women and men. It means equality of interests, obligations and opportunities of women and men in all spheres of society. This concept does not mean the biological characteristics of women and men. On the contrary, the concept of gender is based on the concept of tasks and functions of women and men in society, public and personal life.